PERFORMANCE AS THE ANCHOR: MITIGATING THE IMPACT OF FINANCIAL RISK AND DISTRESS ON LQ45 STOCK RETURNS IN INDONESIA - Khuzairina, Ina Laila; Miradji, Moh Afrizal; Estiasih, Soffia Pujdi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research aims to analyze the influence of financial risk and financial distress on stock returns of companies indexed LQ45 on the Indonesia Stock Exchange during the 2019-2023 period, taking into account the moderation of company performance (ROA). This research uses three analysis models: a model without a moderating variable, a model with ROA as an independent variable, and a moderation model. Data was obtained from the LQ45 company's financial reports and analyzed using multiple regression. The research results show that interest rate risk has a significant positive effect on stock returns, while financial distress has a significant effect only in the model without moderation. The beta factor does not show a significant influence on stock returns in the three models. Company performance (ROA) does not moderate the influence of beta factors and interest rate risk on stock returns, but does moderate the influence of financial distress on stock returns. These findings provide practical implications for financial managers and investors to pay more attention to interest rate risks and financial distress conditions in making investment decisions. This research also adds theoretical insight into the role of company performance in moderating the influence of financial distress on stock returns. Suggestions for further research include expanding research variables, analysis in other sectors, and using different research methods for a more comprehensive understanding Keywords: interest rate risk, beta factor, financial distress, company performance, stock returns, LQ45